Impact of anticancer drugs price cut on physician’s prescription choices on first-line chemotherapy regimens and health expenditure for advanced non-small cell lung cancer in China - Li, Bei; Li, Mei-Ying; Sun, Luan-Luan; Wang, Jian; Zheng, Yan-Qing; Hao, Jing (Journal of Thoracic Disease, 2016)
Background: Increases in insurance coverage and price cut of drugs are two important measures to make health care more accessible and affordable. As far as we know, this was the first study to explore the impact of anticancer drug price cut on health expenses and oncologist’s prescription decisions in China. Methods: The 511 non-small cell lung cancer (NSCLC) patients were recruited from Qilu Affiliated Hospital of Shandong University from January 1, 2003 to December 31, 2010. We categorized the patients into five groups based on China’s fifth population census in 2000, including administrative group, workers and services group, peasants group, professionals group and others group. All statistical analyses were performed using SPSS (version 16.0), all statistic tests were two-tailed and P value ≤0.05 was considered significant. Results: As for the first-line chemotherapy regimens prescribed during the study, 27.6% patients received vinorelbine + cisplatin (NP), 31.5% and 30.9% patients had gemcitabine + cisplatin (GC) and docetaxel + cisplatin (DC), respectively, while only 4.3% patients received paclitaxel + cisplatin or carboplatin (TP). Before price policy implementation, NP was the most popularly used regimen (44.6%). By contrast, doctors’ prescription choices changed significantly after drug price cut, GC took first place (42.0%). GC became the most expensive regimen (4,431.40 RMB per cycle, about 665.15 dollars per cycle), while NP cost the least (1,974.48 RMB per cycle, about 296.37 dollars per cycle) after price cut. No significant reduction could be seen for both the pharmaceutical spending and total expense per inpatient episode after drug price adjustment. One interesting phenomena was that doctors relied less on patient’s sex, age, histology to make their decisions, by contrast, more on patient’s occupation and health insurance type. And, the total drug cost was closely related to patient occupation and health insurance type. Conclusions: The introduction of anticancer drug price control policy was found to be ineffective on the containment of hospital drug expenditures in one cancer center in China.